The Role of Small Firms in China's Technology Development - Nannan Lundin; Fredrik Sjöholm; He Ping; Jinchang Qian (Research Institute of Industrial Economics (IFN), 2007)
Science & Technology (S&T) is high on the Chinese policy agenda but there are large uncertainties on the actual S&T development. For instance, previous studies tend to focus only on large and medium-sized enterprises (LMEs). The situation in Chinese small firms is far less explored. This paper aims to examine the role of S&T-based small firms. More precisely, we examine how much S&T that has been accounted for by small firms and how their S&T intensity differs across industries and ownership groups. We also analyze how various firm characteristics differ over size categories and S&T status. This study is based on newly processed micro level data provided by the National Bureau of Statistics with information on a large number of S&T indicators for small-, medium-, and large-sized manufacturing firms in China in 2000 and 2004. Our results suggest that small firms in Chinese S&T resemble their role in many other countries. They account for a comparably small share of total S&T and most small firms are not engaged in any S&T. However, those small firms that do engage in S&T tend to be more S&T intensive and have a higher output in terms of patents than larger Chinese S&T firms.
Keywords: O30; O31; O53; 330; Technology; SMEs; China; S&T; R&D; KMU; Technischer Fortschritt; Industrielle Forschung; Innovation; China